Local Experiences and Global Commitments in Citizenship Education and Adult Learning in Communities - Heribert Hinzen; Carina Klement; Jaka Klun; Balázs Németh (Universidade de Lisboa, 2022)
The article is based on contributions to the Adult Education Academy of the University of Würzburg and partners in 2021. The authors met in the joint work on active citizenship which is a key issue for the UNESCO World conference on adult learning and education. They take a comparative look into examples from their four home countries: Austria, Germany, Hungary and Slovenia. Their experiences are quite diverse with respect to history, governance, structure, programmes, and activities. Even the names and terms used differ: folk high schools, cultural houses, study circles. These have much in common, such as community-based learning opportunities for youth and adults. UN Member States and UNESCO have adopted global commitments towards institutionalised learning arrangements for communities which will be part of the comparative analysis.